PENERAPAN KETERAMPILAN MENGAJAR DALAM UPAYA PENCAPAIAN HASIL BELAJAR MAHASISWA - Nurdin Mansur (Lantanida Journal, 2016)
The purpose of the implementation of teaching and learning is for learning achievement, both in terms of process and in achieving the outcome is always influenced by various factors. To get the learning outcomes in a subject that is better then relates all factors of educators in the mastery and application of various teaching skills of learning such as the following, namely: a skill as opening lesson, questioning skills, skills to provide reinforcement, skills provide variety, skill explains, small group discussion guiding skills, classroom management skills, teaching skills of individuals, and closing skills lessons. Moreover, in studying a subject willing learners are required to carry out exercises to add a sense of confidence, a strong will to implement appropriate learning strategies, planning and good self-regulation in order to achieve high learning outcomes.